Techno-Economic Analysis Utilization of On-Grid Solar Photovoltaic Systems in Improving Energy Efficiency in Manufacturing Industries - Mochamad Irlan Malik; Andi Adriansyah; Abu Ubaidah Shamsudin (Asosiasi Staf Akademik Perguruan Tinggi Seluruh Indonesia (ASASI), 2023)
Energy efficiency is a critical factor in the success of the manufacturing industry in the era of globalization and increasing competition. One alternative to reduce dependence on conventional energy sources is to utilize Solar Power Plants. This research focuses on the analysis of the techno-economic utilization of on-grid solar photovoltaic (PV) systems in improving energy efficiency in manufacturing industries using Homer Pro software. The study utilizes data on electricity consumption before and after the use of PV panels on a low voltage 33 kVA customer grid for one year. The results show that after the use of On-Grid Photovoltaic System, electricity costs decreased by 16.935.541 IDR or about 15%. The percentage of On-Grid Photovoltaic System usage reached 15.6%, while the grid usage reached 84.4%. Therefore, this study recommends the use of on-grid solar photovoltaic systems as an alternative energy-saving solution in manufacturing industries. However, in designing On-Grid Photovoltaic System, it is crucial to consider the power of the grid and the loads that will be backed up by On-Grid Photovoltaic System.